Bioactive compounds, antioxidant and antimicrobial activities of some fruits and vegetable peel enriched as a functional food in meat technology during frozen storage - Alshehry, Garsa (Italian Journal of Food Science, 2025)
In this work, the impacts of Cucumis melo rind powder (CMRP), Red prickly pear (RPP), and Cider apple pomace (CAP) were evaluated in terms of profiling of bioactive compounds. It could be concluded that the addition of different concentrations of RPP, CMRP, and CAP improved the quality criteria and significantly (P ≤ 0.05) increased the values of total phenolic compound (TPC), antioxidant activity, and fiber content of beef burger during frozen storage. The antioxidant effects of RPP, CMRP, and CAP to retard protein and lipid oxidation were investigated in beef burgers during frozen storage at −18 ± 2°C for 6 months. Powders of RPP rind, CMRP, and CAP were incorporated into freshly minced beef at different concentrations (RPP: 1, 2, and 3%; CMRP: 2, 3, and 4%; and CAP: 2, 4, and 5%) and compared with the control sample. Chemical compositions of the prepared beef burgers, total volatile nitrogen (TVN), thiobarbituric acid (TBA) reactive substances, TPC, and antioxidant activity (DPPH) were determined. Results indicated that powders showed high phenolic content and antioxidant activity, especially RPP. The addition of different concentrations of RPP, CMRP, and CAP caused high storage stability and reduced values of TBA and TVN in prepared beef burgers during frozen storage compared to the control sample. Enrichment of red meat with CMRP, RPP, and CAP has improved hygienic and safety properties than unfortified products without leading to changes like rapid spoilage and consequent reduction in shelf life.